2012
DOI: 10.1088/0953-2048/25/6/065019
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural magnetic phases in superconducting FeTe0.65Se0.35

Abstract: In this paper, we address a number of outstanding issues concerning the nature and the role of magnetic inhomogenities in the iron chalcogenide system FeTe 1-x Se x and their correlation with superconductivity in this system. We report morphology of superconducting single crystals of FeTe 0.65 Se 0.35 studied with transmission electron microscopy, high angle annular dark field scanning transmission electron microscopy and their magnetic and superconducting properties characterized with magnetization, specific … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 53 publications
4
50
0
Order By: Relevance
“…The jump is observed earlier by other researchers in much stronger fields and is associated with the presence of a magnetostructural transition in the layers of the magnetic impurity Fe 3 O 4 . 6 The difference in amplitude can be explained similar to the difference in the M f component in the total magnetization, as discussed above.…”
Section: Experiments Set-upmentioning
confidence: 78%
See 1 more Smart Citation
“…The jump is observed earlier by other researchers in much stronger fields and is associated with the presence of a magnetostructural transition in the layers of the magnetic impurity Fe 3 O 4 . 6 The difference in amplitude can be explained similar to the difference in the M f component in the total magnetization, as discussed above.…”
Section: Experiments Set-upmentioning
confidence: 78%
“…9 This deviation can be associated with the presence, and the spatial distribution, of magnetic inclusions in the superconducting sample, which exist in this compound and others like it. 10 These inclusions can be Fe 3 O 4 and Fe 7 Se 8 , 6 located in the interlayer space of the sample. As a result, the total magnetization of the sample M can be represented as two terms…”
Section: Experiments Set-upmentioning
confidence: 99%
“…In the XR diffraction patterns we identified the Fe 1-y Se (00l) and (l0l) families and the (00l) one for the a nanoscale intergrowth of both phases and its shape and size depends on the crystal growth parameters [6].…”
Section: Iiib4 Microstructural Angular Investigationmentioning
confidence: 94%
“…X-ray studies have shown that the sample contains magnetite (Fe 3 O 4 ) impurity (less than 0.3 per cent of the sample mass), which can be responsible for the appearance of the feature observed in Fig. 2 at T = 120 К [7].…”
Section: Resultsmentioning
confidence: 99%